A cobalt phosphide catalyst for the hydrogenation of nitriles. Issue 26 (11th June 2020) - Mitsudome, Takato; Sheng, Min; Nakata, Ayako; Yamasaki, Jun; Mizugaki, Tomoo; Jitsukawa, Koichiro
Abstract : A well-defined nano-cobalt phosphide serves as an air-stable, highly active and reusable heterogeneous catalyst for the selective hydrogenation of nitriles to primary amines under mild reaction conditions. Abstract : The study of metal phosphide catalysts for organic synthesis is rare. We present, for the first time, a well-defined nano-cobalt phosphide (nano-Co2 P) that can serve as a new class of catalysts for the hydrogenation of nitriles to primary amines. While earth-abundant metal catalysts for nitrile hydrogenation generally suffer from air-instability (pyrophoricity), low activity and the need for harsh reaction conditions, nano-Co2 P shows both air-stability and remarkably high activity for the hydrogenation of valeronitrile with an excellent turnover number exceeding 58000, which is over 20- to 500-fold greater than that of those previously reported. Moreover, nano-Co2 P efficiently promotes the hydrogenation of a wide range of nitriles, which include di- and tetra-nitriles, to the corresponding primary amines even under just 1 bar of H2 pressure, far milder than the conventional reaction conditions. Detailed spectroscopic studies reveal that the high performance of nano-Co2 P is attributed to its air-stable metallic nature and the increase of the d-electron density of Co near the Fermi level by the phosphidation of Co, which thus leads to the accelerated activation of both nitrile and H2 . Such a phosphidation provides a promising method for the design of an advanced catalyst with high activity and stability in highly efficient and environmentally benign hydrogenations.